RELIGIONS IN THE CONSTITUTION OF ASEAN COUNTRIES: The Rule of Law and Welfare Concept - Asari Taufiqurrohman (International Journal of Law, Environment, and Natural Resources, 2021)
The study of the constitution could not be covered by the scope of one state only, but also  compare it with others. To strengthen cooperation between ASEAN community, we should understand the constitutional concept which follows the rule of law. Even adopted by the majority of nation-state according to with their basic type of the country and nationality (such as neko77 culture, religion or norms). To compare it, we have to discuss a more significant idea about the state. This research promoted to explain about the extent of religious content as well as prime religion which recognized on the constitution of the ASEAN countries by using normative legal research, with emphasizes result by comparison among countries. Finally, this research describes how important the religion concept (in each manuscript) to the body of the constitution, to reach “the living constitution” and to show the other side of the welfare concept in ASEAN countries with various theories of laws. The approach method is related to doctrinal legal research.